New and unusual Pd-Tl-bearing mineralization in the Anomal'nyi deposit, Kondyor concentrically zoned complex, northern Khabarovskiy kray, Russia. (2nd January 2018) - Barkov, Andrei Y.; Shvedov, Gennadiy I.; Polonyankin, Alexander A.; Martin, Robert F.
Abstract: New Pd-Tl-(Bi, As)-rich compounds are described from the Anomal'nyi Cu-PGE deposit, Kondyor alkaline ultramafic complex, northeastern Russia. They occur in vein-type settings associated with bodies of 'kosvite' (magnetite-rich clinopyroxenite) in the dunite-(peridotite) core, in pegmatiticand micaceous rocks. The ore zones are substantially enriched in phlogopite; they consist of diopside, disseminated titaniferous magnetite and fluorapatite (Sr-bearing). The observed assemblages of ore minerals include sulfides of the chalcopyrite-bornite-(secondary chalcocite) associationand various species of platinum-group minerals (PGM) [isomertieite or arsenopalladinite rich in Sb, mertieite-II, mertieite-I, sobolevskite, kotulskite, merenskyite, zvyagintsevite, palarstanide, paolovite, sperrylite, maslovite or moncheite, hollingworthite and unnamed species of PGM] anda Ag-Au alloy. The oxides [Pd4 (Bi, Te, Tl)O6 and Pd4 (Tl, Bi, Te)O6 ] probably formed in situ by oxidation reactions at the expense of the associated PGM intergrowths. These involve palladium bismuthide-thallide phases, Pd5 (Tl, As, Bi)and Pd5 (As, Tl, Bi), which are documented here for the first time. A fairly evolved environment, enriched in Cu, Pd, Te, Bi, Pb and volatile components, is indicated for the vein-type deposit at Anomal'nyi.